2019
DOI: 10.1088/1742-6596/1235/1/012094
|View full text |Cite
|
Sign up to set email alerts
|

Fish Species Classification Using Probabilistic Neural Network

Abstract: The number of varieties of fish species in the same family causes difficulties in classifying fish species directly. Currently, the process of fish species classification accomplished in the fisheries section uses direct eye observations and knowledge assumption and then compares the existing characteristics with reference books. Therefore, an image processing and neural network approach are needed to classify fish species effectively and efficiently. In this study, there are three fish species classified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Research by Andayani, et al (2018) used three types of fish in the Scombridae family which were classified using the Neural Probabilistic Network method with an accuracy rate of 89.65% using 112 training data images and 29 image data testing [11].…”
Section: Methodsmentioning
confidence: 99%
“…Research by Andayani, et al (2018) used three types of fish in the Scombridae family which were classified using the Neural Probabilistic Network method with an accuracy rate of 89.65% using 112 training data images and 29 image data testing [11].…”
Section: Methodsmentioning
confidence: 99%
“…Liang et al [3] 2020 Shape features Convolutional neural network 98.1% Knausgård et al [4] 2022 Generic features Convolutional neural network 87.74% Böer et al [5] 2021 Morphological features DeepLabV3 and PSPNet models 96.8% Iqbal et al [6] 2019 Generic features AlexNet model 90.48% Cui et al [7] 2020 Generic features Convolutional neural network 97.5% Zhang et al [8] 2021 Morphological features Convolutional neural network 96% Montalbo and Hernandez [9] 2019 Generic features VGG16 DCNN Model 99% Mathur and Goel [10] 2021 Generic features ResNet-50 Model 98.44% Ahmed et al [11] 2022 Statistical & color features SVM classifier 94.12% Lan et al [12] 2020 Shape and texture features Deep CNN 89% Allken et al [13] 2018 Shape features A deep learning neural network 94% Andayani et al [14] 2019 In this paper, RBFNN and SVM techniques for fish image classification were presented and evaluated against the fish shape features. The contribution of this work can be summarized as: -Extracted robust features for fish image classification.…”
Section: 6%mentioning
confidence: 99%
“…In this work, a novel training regime is developed to cue the scarcity of training data and achieved a classification rate of 94%. Andayani et al [14] used a combination of geometric invariant moment, gray-Level co-occurrence matrix (GLCM), and hue saturation value (HSV) feature extraction methods to extract fish images features and for fish species classification purposes, they used probabilistic neural network (PNN) method utilized to properly classify fish species and achieved 89.65% accuracy rate. Others utilize convolutional neural networks (CNN) using deep learning for fish classification [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that it could classify poisonous or non-poisonous fishes. In addition, research on fish classification has also been carried out using an image processing approach and an artificial neural network to classify fish species effectively and efficiently using a Probabilistic Neural Network with an 89.65% classification accuracy [12].…”
Section: Introductionmentioning
confidence: 99%